HYDROGEOLOGIC FACTORS AFFECTING GAS CONTENT DISTRIBUTION IN COAL BEDS - Scott A.R. (My University, 2002)
Gas content in coal is not fixed but changes when equilibrium conditions within the reservoir are disrupted. Therefore, gas content distribution in coal varies laterally within individual coal beds, vertically among coal beds in a single well, and within thicker coal beds. Major hydrogeologic factors affecting gas content variability include gas generation, coal properties, and reservoir conditions. Gas generation affects gas content variability on a regional scale, whereas coal properties influence gas content distribution on a regional and local scale. Reservoir conditions affect gas content more locally within specific fields or individual wells. The potential for high gas content is controlled directly by the amount of thermogenic and secondary biogenic gases generated from the coal which in turn are controlled by burial history, maceral composition, and basin hydrodynamics. Variability in mineral matter (ash) and moisture content, sorption behavior among macerals, diffusion coefficients, and permeability result in heterogeneous gas content distribution. Gas content decreases with decreasing pressure and temperature, and coal beds become undersaturated with respect to methane during basin uplift and cooling. Gas content generally increases where conventional and hydrodynamic trapping of coal gases occur and may decrease in areas of active recharge with downward flow potential and/or convergent flow where there is no mechanism for entrapment.
Keywords: HYDROGEOLOGIC FACTORS; GAS CONTENT DISTRIBUTION; COAL BEDS